The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1073/pnas.97.8.4186
|View full text |Cite
|
Sign up to set email alerts
|

The function of the human homolog of Saccharomyces cerevisiae REV1 is required for mutagenesis induced by UV light

Abstract: In Saccharomyces cerevisiae, most mutations induced by a wide range of mutagens arise during translesion replication employing the REV1 gene product and DNA polymerase . As part of an effort to investigate mammalian mutagenic mechanisms, we have identified cDNA clones of the human homologs of the yeast REV genes and examined their function in UV mutagenesis. Previously, we described the isolation of a human homolog of yeast REV3, the catalytic subunit of pol , and here report the identification and sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 32 publications
7
115
0
Order By: Relevance
“…There was also no observed difference in sensitivity to UV radiation between the knockdown cell line and the parental controls. Diminished mutagenesis without a significant change in cell survival was similarly observed for a foreskin fibroblast cell line expressing REV1 antisense RNA and treated with UV radiation [60]. The greater relative effect on mutagenesis compared to survival is analogous to the situation in yeast, indicating alternative pathways to increase survival.…”
Section: Consequences Of Rev3l Rev1 and Rev7 Reduction In Human Cellmentioning
confidence: 69%
“…There was also no observed difference in sensitivity to UV radiation between the knockdown cell line and the parental controls. Diminished mutagenesis without a significant change in cell survival was similarly observed for a foreskin fibroblast cell line expressing REV1 antisense RNA and treated with UV radiation [60]. The greater relative effect on mutagenesis compared to survival is analogous to the situation in yeast, indicating alternative pathways to increase survival.…”
Section: Consequences Of Rev3l Rev1 and Rev7 Reduction In Human Cellmentioning
confidence: 69%
“…The Rev1 structure and functions appear to be highly conserved in higher eukaryotes. Experimental reduction of REV1 expression in cultured human cells results in a decrease in UV-induced mutagenesis [98]. Polη in yeast is encoded by RAD30, whose inactivation [99] or mutations in the corresponding mammalian xeroderma pigmentosum variant (XPV) gene [100,101] lead to an increased susceptibility to UV-induced DNA damage.…”
Section: Y Family Dna Polymerasesmentioning
confidence: 99%
“…Several studies using small interfering RNA on mammalian TLS polymerases have shown that Rev1 and Rev3, but not Pol , are clearly required in UV-induced mutagenesis (9,19,20,26,35). However, it is currently unknown what kind of mechanism is involved in the observed hypermutability of XP-V cells.…”
Section: Role For Pol In Prevention Of Uv-induced Mesenchymal Tumorsmentioning
confidence: 99%